Die Zukunft der Derivation oder: Derivation 2.0 - Fuhrhop, Nanna; Werner, Martina (Linguistik Online, 2016)
Traditionally, contemporary German is considered to be rich in affixes which is displayed by a wide range of e. g. nominal suffixes (such as -ung, -heit, -nis, -tum, -sal). However, productivity tests, especially with non-native lexemes, challenge this view since many formal restrictions between affixes and different word classes can be formally identified – synchronically and diachronically – and which cannot be explained by traditional approaches. This paper questions the general morphological productivity of derivation coinciding with a decrease of nominal, adjectival and verbal affixation and, in parallel, pointing to morphological alternatives. In this view, a process of an increasing “syntactification” (as it will be called) is taking place resulting in a morphological preference for conversion. Diachronically, the morphological development from compounding to derivation is well-described. The question as to why and how conversion emerges, especially in an inflectional language, and how it is linked to former or coexisting morphological types, here derivation, has never been asked – though important observations from language typology have been made. Against this background, the process of syntactification fills this research lacuna, also in a morpho-theoretical way, since it can be interpreted as an ongoing language change consisting of a change in linguistic encoding.